Impact of Environmental Advertising on Customers’ Patronage Decision in Nigeria Banks - Ibidunni Oyebisi; Afisanwo Adetayo; Ibidunni Stephen (MultiTech Publisher, 2023)
This research examined the impact of Environmental Advertising on Customer’s Patronage Decision in Nigerian Banks. The study population was 384 out of which a total of 250 representing 65.1% was retrieved from the various respondents who are customers of the Tier 1 banks in Nigeria. Data collected was analysed using the Simple Regression Technique and this was done with the aid of Statistical Package for Social Sciences (SPSS) 21. The result of the tested hypothesis using the Simple Regression Technique showed a p value less than 0.005 which indicates the rejection of the null hypothesis and the acceptance of the alternate hypothesis that states that Environmental response has a significant impact on customer’s patronage decision of Nigerian banks.